2008
DOI: 10.1148/rg.287085033
|View full text |Cite
|
Sign up to set email alerts
|

US-guided Fine-Needle Aspiration of Thyroid Nodules: Indications, Techniques, Results

Abstract: Fine-needle aspiration (FNA) biopsy of thyroid nodules is minimally invasive and safe and is usually performed on an outpatient basis. However, the optimal application of FNA requires not only technical skill but also an awareness of the limitations of the procedure, the indications for its use, the factors that affect the adequacy of the biopsy specimen, and the postprocedural management strategy. Ultrasonographic (US) features that are considered indications for FNA include single and multiple thyroid nodule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
148
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(159 citation statements)
references
References 76 publications
0
148
1
10
Order By: Relevance
“…US-FNA of thyroid nodules is a simple, minimally invasive, and safe procedure, usually performed in the outpatient clinic (2). The most common complications are local pain or discomfort and minor hematomas (4,6).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…US-FNA of thyroid nodules is a simple, minimally invasive, and safe procedure, usually performed in the outpatient clinic (2). The most common complications are local pain or discomfort and minor hematomas (4,6).…”
Section: Discussionmentioning
confidence: 99%
“…If the patient is taking an anticoagulant or antithrombotic, stopping the medication for 3 -10 days is recommended before and after US-FNA (4,5,9,11,17,18). However, performing US-FNA in patients taking anticoagulant or antithrombotic remains controversial and lacking in evidence, such as randomized controlled study (2,4,7,9,16,33). A recent study of 593 patients who underwent US-FNA on a total of 788 neck lesions reported no significant differ- ences in hematoma formation between patients who were on antithrombotic medications and those who were not (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations